Modul Pelatihan Kecerdasan Moral Untuk Siswa SMK - Mira Komariah; Siti Muhibah Muhibah; Arga Satrio Prabowo (GUIDING WORLD (BIMBINGAN DAN KONSELING), 2024)
The research was conducted on the basis of the researcher's concern that adolescent morals are declining. This research and development aims to find out how to develop a moral intelligence training module for students at SMK Negeri 4 Pandeglang. The method used in this research is Reseacrh and Development (R&D). This research procedure uses the 4D model, namely (1) Define, (2) Design, (3) Develop, and (4) Disseminate.The prototype test of moral intelligence module was conducted at SMK Negeri 4 Pandeglang. The test results from the material content amounted to 83.3%, the language readability test amounted to 90%, the learning media test amounted to 93.1%, and the practitioner's perception amounted to 100%. In general, the module is said to be feasible with an average score of 92%. After the trial, there was an effect of the module media on increasing students' moral intelligence